Holographic Interferometry for Measuring the Effect of Thermal Modification on Wood Thermal Properties - Áron Hortobágyi; Elena Pivarčiová; Pavol Koleda (Applied Sciences, 2021)
The paper focuses on the use of holographic interferometry in the research of thermal modification and its effect on the heat transfer from the wood surface to the surrounding air. In the experiment, spruce wood samples modified at 160 °C, 180 °C, 200 °C, 220 °C and an unmodified control sample were used. A radiant heat source was placed under the sample. The top of the sample represented the boundary where the observed heat transfer occurred. The temperature fields above the sample were visualized by real-time holographic interferometry and the heat transfer coefficient α was calculated from the obtained interferograms. During the heating of the samples, a decrease of the heat transfer coefficient was observed. The heat transfer coefficient of the control unmodified sample decreased from a maximum of α = 22.66 Wm–2K–1 to a minimum of α = 8.6 Wm–2K–1. In comparison with these values, the heat transfer coefficients of the modified samples treated at 160, 180, 200 and 220 °C, respectively, decreased to 99%, 93%, 68% and 51% of the maximal control value at the beginning of experiment and to 95%, 86%, 80% and 64% of the minimal control value by the end of the experiment. Moreover, an analysis of variance was used to determine the significance of the heat treatment effect on the heat transfer coefficient. A high significance (p < 5%) was observed between the control sample and the modified samples treated at 200 °C and 220 °C. Experiments with the use of holographic interferometry produced results consistent with previous studies conducted by different methods.